FAKTOR YANG BERHUBUNGAN DENGAN KEBERADAAN JENTIK AEDES AEGYPTI (STUDI KASUS DI KELURAHAN SUKOREJO, KECAMATAN GUNUNGPATI, KOTA SEMARANG TAHUN 2014) - Santi, Daka; Budiyono, Irwan; Wahyono, Bambang (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
The larvae existence of a region, were influenced by some factors. The purpose of this study was to determine what factors are associated with the presence of Aedes aegypti mosquito larvae in RW II Sukorejo. This type of research was explanatory research with cross sectional study. The population in this study were all families in the village Sukorejo RW II. This study used random sampling technique to obtain sample that are 66 households in RW II. Instrument in this study were questionnaire and a check list. Data analysis was performed byunivariate and bivariate (withchi square test p <005). Result obtained that there was a relationship between the mosquito nest extermination with the presence of larvae (p = 0.001), there was no relationship between the frequency of monitoring officers visit to the presence of larvae(p = 1.000), there was a relationship between the presence of wide water reservoirs (p = 0.018), and there was a relationship between the presence ofgarbage with the presence of larvae (p = 0.035). Conclusion there was a relationship between implementation mosquitonest extermination, water reservoirs, and garbage with the presence of larvae. Suggestions to growing up the mosquito nest extermination in Sukorejo for protect to find larvae.